SAT0494 Long-Term Retention and Predictors of Anti-Tnf Treatment Response in Juvenile Idiopathic Arthritis: Data from Reuma.PT, a Nation-Wide Register. (9th June 2015) - Mourão, A.F.; Santos, M.J.; Melo Gomes, J.A.; Martins, F.; Mendonça, S.; Ramos, F.O.; Fernandes, S.; Salgado, M.; Guedes, M.; Carvalho, S.; Costa, J.A.; Brito, I.; et al.
Abstract : Objectives: To assess the effectiveness and safety of biological therapy as well as predictors of response after 1 year of therapy, the retention rate in biological treatment and predictors of drug discontinuation in JIA patients registered in the Portuguese register of rheumatic diseases, Reuma.pt. Methods: We collected prospectively patient and disease characteristics from patients with JIA who started biological disease modifying antirheumatic drugs. Adverse events were collected during the overall follow-up period. The predictors of response at 1 year were assessed and drug retention rates were calculated at 4 years of treatment for the first biologic agent using the Kaplan-Meier method. Results: Of the 812 JIA patients registered in Reuma.pt, 227 received biological therapy. The mean age at disease onset was 7.5±4.9 years and the mean age at the beginning of biological therapy was 16.2±9.4 years. The most common JIA category on biologics was polyarticular rheumatoid factor (RF) negative (23.3%). Most patients (90.3%) were treated with an anti-TNF as first biologic (etanercept, 69.2%). Disease activity decreased significantly at 6 months and 1 year of treatment. Fourteen patients discontinued biological therapies during the follow-up period due to adverse events. Baseline JADAS10 was the strongest predictor of treatment response at 1 year of biological therapy, with a 0.73 decrease for each unit increase at baseline (95% CI 0.45-1.10, p<0.001). Retention rates for the first biological agent were: 92.9% at 1 year, 85.5% at 2 years, 78.4% at 3 years and 68.1% at 4 years of treatment. Among all JIA subtypes, only concomitant therapy with corticosteroids was found to be univariately associated with withdrawal of biological treatment (p=0.016). Conclusions: Data from Reuma.pt confirm that biological therapies are effective and safe in patients with JIA. Additionally, baseline disease activity was the strongest predictor of treatment response and the retention rates for the first biological agent are high throughout 4 years. Disclosure of Interest: None declared